Evaluation of the activated clotting time and activated partial thromboplastin time for the monitoring of heparin in adult extracorporeal membrane oxygenation patients. (September 2014) - Atallah, S; Liebl, M; Fitousis, K; Bostan, F; Masud, F
Introduction: Historically, the activated clotting time (ACT) has been the preferred monitoring test of the heparin effect in extracorporeal membrane oxygenation (ECMO) patients. However, few adult studies have evaluated its correlation to the heparin dose or other monitoring tests, such as the activated partial thromboplastin time (aPTT). This retrospective study sought to evaluate the correlation between the heparin dose and these monitoring tests. Methods: Patients administered a heparin drip during ECMO were included in this study. The primary endpoints were the correlation between heparin dose and ACT or aPTT and the relationship between paired ACT and aPTT samples. Results: Forty-six patients met the criteria for study inclusion. A better correlation was observed for heparin dose and aPTT (Pearson product-moment correlation coefficient ( r ) = 0.43 – 0.54) versus ACT ( r = 0.11 – 0.14). Among the paired sample data, ACT values did not differ significantly between Groups two (aPTT 60 – 75 seconds) and three (aPTT >75 seconds). Conclusion: The heparin dose correlated better with aPTT relative to ACT and, thus, may be considered a more effective tool for the dosing of heparin in adult ECMO patients. Paired ACT and aPTT sample data suggested a poor relationship between these two anticoagulant monitoring tests.